Metropolitan Eco-Regimes and Differing State Policy Environments: Comparing Environmental Governance in the Portland–Vancouver Metropolitan Area. Issue 6 (November 2018) - Thiers, Paul; Stephan, Mark; Gordon, Sean; Walker, Alexander
The Portland Metropolitan region, a single economic and ecological region with a bifurcated state and local governance structure, provides an opportunity to compare governance models and state policy environments in a single region. Using stakeholder interviews and secondary sources, we examine the role of state government policy in shaping and supporting different regimes. We find that Portland exhibits a stable, "smart-growth" regime that we characterized as a metropolitan eco-regime whereas Vancouver is in a period of fragmentation without a stable metropolitan regime. This is best explained by the differing state-level regulatory contexts and the different forms of polycentricity influenced by state action. Differences in regime and governance structure result in differently drawn and expanded urban growth boundaries with subsequent differences in land-use outcomes. We conclude with observations about state-level action and subsequent forms of polycentricity to support metropolitan eco-regimes.